UTILIZATION OF BANANA FRONDS AS CREATIVE CRAFTS AND ITS BUSINESS OPPORTUNITIES (CASE STUDY OF SERVICE ACTIVITIES IN THE PKK GROUP OF PEUKAN BADA DISTRICT): PEMANFAATAN PELEPAH PISANG SEBAGAI KERAJINAN KREATIF DAN PELUANG USAHANYA (STUDI KASUS KEGIATAN PENGABDIAN DI KELOMPOK PKK KECAMATAN PEUKAN BADA) - Risa Nursanty; Yunita; Rina Kurniaty (PT. ROCE WISDOM ACEH, 2025)
Bananas are a cultivated crop that has been cultivated for a long time in Southeast Asia. They are readily available in Indonesia, particularly in the province of Aceh. Utilization of banana stem parts is still less than that of the leaves and fruit. One potential business opportunity is to utilize banana stem waste to create innovative crafts, such as pencil cases, tissue boxes, decorative flowers, wallets, and other similar items. The methods used include training and a respondent survey. The training was conducted with teenagers and homemakers from the Family Welfare Movement (PKK) group in Peukan Bada District. A study was conducted to assess the feasibility of craft products among 30 respondents from various segments. Creative crafts utilizing banana stem waste offer potential opportunities for development in Aceh Province, given the abundance of banana trees.